2020
DOI: 10.3389/fphar.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

A Penicillin Derivative Exerts an Anti-Metastatic Activity in Melanoma Cells Through the Downregulation of Integrin αvβ3 and Wnt/β-Catenin Pathway

Abstract: The synthetic triazolylpeptidyl penicillin derivative, named TAP7f, has been previously characterized as an effective antitumor agent in vitro and in vivo against B16-F0 melanoma cells. In this study, we investigated the anti-metastatic potential of this compound on highly metastatic murine B16-F10 and human A375 melanoma cells. We found that TAP7f inhibited cell adhesion, migration and invasion in a dose-dependent manner. Additionally, we demonstrated that TAP7f downregulated integrin avb3 expression and Wnt/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Investigation of the 3D tumor spheroid penetration study showed higher cellular absorption of DMSA-conjugated APG nanoparticles as compared to the unconjugated nanoparticles. Thiol-containing DMSA can directly bind to cysteine of beta integrin receptors of the cells, , and that probably led to higher permeation and greater bioavailability of APG from DMSA-conjugated APG-NPs. Further, our investigation is also supported by the findings of Zhang et al that DMSA conjugation to nanoparticles improved bioavailability of nanoparticles …”
Section: Discussionmentioning
confidence: 99%
“…Investigation of the 3D tumor spheroid penetration study showed higher cellular absorption of DMSA-conjugated APG nanoparticles as compared to the unconjugated nanoparticles. Thiol-containing DMSA can directly bind to cysteine of beta integrin receptors of the cells, , and that probably led to higher permeation and greater bioavailability of APG from DMSA-conjugated APG-NPs. Further, our investigation is also supported by the findings of Zhang et al that DMSA conjugation to nanoparticles improved bioavailability of nanoparticles …”
Section: Discussionmentioning
confidence: 99%
“…In a preceding study, (2) we reported that derivative containing the dipeptide Leu-Phe (TAP7f, Figure 1), behaves as a selective and potent antitumor agent that induces an apoptotic response. (3,4) In order to support downstream research activities with this candidate, we were initially requested to prepare increasing amounts of TAP7f. Herein we describe the strategy chosen to achieve that goal.…”
Section: Introductionmentioning
confidence: 99%